Design of automatic control system to control the flow of biogas fuel into internal combustion system - Mohamad Saufi, Ayob (2010)
This work is to analyze the parameter and variables that used to design an automatic control system to control biogas fuel in internal combustion engine. The objective of this thesis is to design the automatic control system. It shows that for governed engines, the governor maintains constant engine rpm by moving the throttle to control fuel supply to the engine and match power output to the engine load. The function of the mechanical governor is to adjust the fuel valve angle so the load on the engine will maintain the desired engine rpm at the horsepower setting selected. Performance of the designed automatic control system was investigated and the effect of the automatic control system to the internal combustion engine predicted. System analysis for the project were done by using manual calculation to set the displacement and force affected by the governor and the size opening of the valve and also using FORTRAN code to analyze the speed and position of the mechanical governor by using certain input speed that have been decided. In conclusion, this thesis aim to explain the significant of the automatic control system that have been designed and describe how the system can manage to maintain the optimum speed during steady state and transient condition.